A Framework of Factors Influencing Intention for Sustainable Entrepreneurship on Micro, Small, And Medium Enterprises (MSMEs): Mediating Effect of Entrepreneurial Opportunity Recognition - Ismadi, Muhammad Iszaruddin; Koe, Wei Loon; Mahphoth, Mohd Halim (Business and Economic Research, 2023)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The concept of sustainable entrepreneurship has received much attention recently as a remedy for the issue of environmental deterioration. Malaysia's degradation of the environment is an issue that requires global concern. Manufacturing and entrepreneurial endeavours have been shown to impact the issues substantially. Micro, small, and medium-sized enterprises (MSMEs), notably those in Malaysia, must be made aware of sustainable entrepreneurship due to a lack of knowledge and awareness. Since intention may reflect behaviour, this study aims to identify elements or factors that may influence MSMEs' intentions for sustainable entrepreneurship. The element consists of sustainable attitude, sustainable value, sustainable orientation, social norms, and government legislation. Additionally, this study makes an effort to investigate how opportunity recognition functions as a mediator in the connection.